MAOA Influences the Trajectory of Attentional Development - Lundwall, Rebecca A.; Rasmussen, Claudia G. (Frontiers in Human Neuroscience, 2016)
Attention is vital to success in all aspects of life (Erickson, Thiessen, Godwin, Dickerson, & Fisher, 2015; Meck & Benson, 2002), hence it is important to identify biomarkers of later attentional problems early enough to intervene. Our objective was to determine if any of 11 genes (APOE, BDNF, HTR4, CHRNA4, COMT, DRD4, IGF2, MAOA, SLC5A7, SLC6A3, and SNAP25) predicted the trajectory of attentional development within the same group of children between infancy and childhood. We recruited followup participants from children who participated as infants in visual attention studies and used a similar task at both time points. Using multilevel modeling, we associated changes in the participant’s position in the distribution of scores in infancy to his/her position in childhood with genetic markers on each of 11 genes. While all 11 genes predicted reaction time (RT) residual scores, only MAOA had a significant interaction including time point. We conclude that the MAOA SNP rs1137070 is useful in predicting which girls are likely to develop slower RTs on an attention task between infancy and childhood. This early identification is likely to be helpful in early intervention.